ChemInform Abstract: Palladium(II) Complexes Bearing 2‐(1H‐Imidazol/oxazol‐2‐yl)‐pyridines: Synthesis, Structures and Ligand Effects in Suzuki—Miyaura Cross‐Coupling. Issue 30 (29th July 2014) - Eseola, Abiodun Omokehinde; Geibig, Daniel; Goerls, Helmar; Sun, Wen‐Hua; Hao, Xiang; Woods, Joseph Anthony Orighomisan; Plass, Winfried
Abstract A series of hemilabile 2‐(imidazol‐2‐yl)pyridine and 2‐(oxazol‐2‐yl)pyridine palladium ligands are synthesized, characterized, and their catalytic properties in high‐temperature Suzuki—Miyaura cross‐coupling reactions are investigated.